Movement sensor automatic light and fan / Amir Abas & Mohamad Rafiudin Ramle - Abas, Amir; Ramle, Mohamad Rafiudin (2015)
This is an electronics project on Movement Sensor Automatic Light and Fan using PIR sensors which is used to automate lamp and fan switching. This project developed using arduino microcontroller, de motor as fan and LED as lamp. This project also consist the infrared that can detect human motion in the toilet. The infrared signal will send to the arduino. Then the arduino send the signal to the lamp and fan as in which the both is on. After a few seconds, the lamp and fan will close automatically if no more obstacle to be detected by the infrared sensor. This automatic lamp and fan system is powered by using electricity to switch on and off. This project will contribute a lot of pleasure in our daily life. For those disability and older people, they will appreciate Movement Sensor Automatic Light and Fan. Thus, it saving-up on electricity costs.